Aural rehabilitation program: 10 years of experience at ramathibodi hospital - Krisna Lertsukprasert (2019)
© 2018, Medical Association of Thailand. All rights reserved. Background: A preschool aural rehabilitation program at Ramathibodi Hospital was established in 2001. The main objective was to provide early intervention for deaf children and the opportunity to develop listening, speech, and language skills using residual hearing. Objective: To evaluate the outcomes of the rehabilitation program for hearing impaired children between 2001 and 2011. Materials and Methods: Retrospective analyses of the medical records of 197 hearing impaired children who attended the aural rehabilitation program regularly until they left the program. The questionnaire was completed by their parents. Results: Most of the hearing-impaired children (87.82%) had profound hearing loss. There were 69.54% diagnosed at Ramathibodi Hospital and 30.46% referred from other medical centers. The overall achievement of the rehabilitation program was enabling deaf children to positively and progressively develop their listening, speech, and language skills. Forty-one-point-twelve percent and 30.46% of deaf children participated in mainstream and integrated school respectively. Only 23.35% had to continue studying in deaf school because of the limitation in oral communication. Conclusion: The aural rehabilitation program in the authors’ hospital provided positive progression for deaf children. The program also provided many benefits, such as close monitoring of a child’s skills and immediate management if the child had other problems. Moreover, deaf children received a full range of services from professionals, which were good examples for new parents of deaf children and good role models for teaching communication disorders and to related professionals.